Pengembangan Materi Teks Fabel Berbasis Media Scribe Sparkol di Kelas VII SMP Negeri 1 Pantai Labu - Irawan, Sumba; Umar, Azhar (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This research aims to develop fable text materials for seventh-grade students using the Scribe Sparkol media and assess the product's feasibility. Following the Borg and Gall procedure, the study involved 38 samples, utilizing a Likert Scale for needs and problem analysis, product validation, teacher assessments, student responses, and learning implementation observations. The results indicate the product, "Development of Fable Text Material Based on Scribe Sparkol Media in Class VII of SMP Negeri 1 Pantai Labu," falls within the "very good" category. This is evidenced by a 99% material expert validation, 82% media expert validation, 94% teacher assessment, and 84.33% student responses, all categorized as "very good." Additionally, the teacher's observation during learning implementation yielded a 95% score in the "very good" category. Hence, the product is deemed suitable for integration into the learning process.